Evaluating the impact of training and development on customer service in Namibia : the case study of the Ministry of Veterans Affairs - Endjala, Frankhilde Twiifikeni (Stellenbosch : Stellenbosch University, 2020)
Thesis (MPA)--Stellenbosch University, 2020.